Correct Reasoning Essays on Logic-Based AI in Honour of Vladimir Lifschitz - Erdem, Esra.; Lee, Joohyung; Lierler, Yuliya; Pearce, David; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This Festschrift published in honor of Vladimir Lifschitz on the occasion of his 65th birthday presents 39 articles by colleagues from all over the world with whom Vladimir Lifschitz had cooperation in various respects. The 39 contributions reflect the breadth and the depth of the work of Vladimir Lifschitz in logic programming, circumscription, default logic, action theory, causal reasoning and answer set programming.
Keywords: Computer science; Computer programming; Software engineering; Programming languages (Electronic computers).; Computer logic; Mathematical logic; Artificial intelligence; Computer Science; Mathematical Logic and Formal Languages; Artificial Intelligence (incl. Robotics).; Logics and Meanings of Programs; Software Engineering; Programming Techniques; Programming Languages, Compilers, Interpreters; Electronic books